Perkembangan Wilayah dan Perubahan Tutupan Lahan di Kabupaten Purwakarta sebagai Dampak dari Proses Konurbasi Jakarta-Bandung - Alfin Murtadho; Siti Wulandari; Muhammad Wahid; Ernan Rustiadi (P4W LPPM IPB, 2018)
Jabodetabek and Bandung Raya metropolitan region experienced an urban expansion phenomenon that caused the two metropolitan regions to become increasingly connected by a corridor and form a mega-urban region caused by the conurbation process. Purwakarta regency is one of the regions in Jakarta-Bandung corridor that experienced the impact of Jakarta-Bandung conurbation process. This study aims to analyze the level of regional development, to analyze land cover change that occurred, and to predict Purwakarta Regency land use/land cover in 2030. Regional development analysis is done by using the Scalogram method based on Potential Village data of year 2003 and 2014. Land cover change analysis is done through spatial analysis by overlaying land cover Landsat Satellite Image of year 2000 and 2015. Land use/land cover prediction in 2030 is conducted through spatial modelling of Cellular Automata Markov method. Purwakarta Regency experienced an increase in regional development within the period of 11 years (2003 to 2014), which is marked by a decrease in the percentage of the number of villages that are in hierarchy III and increase in the percentage of the number of villages that are in hierarchy II and I. In general, within 15 years (2000 to 2015) Purwakarta Regency has increasing number of built-up area and mixed gardens, meanwhile dry land, forest, paddy field, and water bodies tend to decrease. The results of CA Markov analysis show that the built-up area is predicted to continue to increase from 2000 to 2030, meanwhile paddy fields and water bodies will continue to decrease.